ANALISIS LIKUIDITAS, PERMODALAN, KEMANDIRIAN DAN PERTUMBUHAN PADA KOPERASI SIMPAN PINJAM (KSP) TOKALAPETA KELURAHAN SUKANAYO KOTA BAUBAU - Rais R, Muhammad (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
This study aims to determine the financial performance of the Savings and Loan Cooperative seen from the ratio of liquidity, capital, independence and growth. The data analysis method used by the author is to calculate the liquidity ratio, capital ratio, independence ratio and growth. The results of the study are: (1) Liquidity Ratio Cash ratio 35.97%, 46.95% and 49.21%. The three-year average is 44.04% indicating a fairly good condition because it is above 10%-15%, meaning that the level of liquidity is good. (2) Capital 16.22%, 19.22% and 18.91%. The three-year average is 18.12% indicating a poor condition because it is below 40%-60%, meaning that the level of capital is not good. (3) Ratio of Independence and Growth. (a) Asset profitability 10.55%, 6.98% and 2.26%. The three-year average is 5.84% indicating a poor condition because it is below 10%, meaning that the level of capital is not good. (b) Own capital profitability 65.06%, 36.30% and 24.96%. The three-year average is 42.11% indicating a very good condition because it is above 5%, meaning that the level of capital is very good.